Remission Can be Achieved in 50% of Early Rheumatoid Arthritis Patients after 25 Weeks in Daily Clinical Practice - Vinall, Maria (MD Conference Express, 2008)
This article discusses results of a prospective, descriptive clinical practice-based study [NCT00122382] that was conducted in a cohort of patients with recent onset RA who were DMARD-naïve. The objective of the study was to evaluate whether a step-up DMARD, tight-control approach could produce remission (defined as DAS28 <2.6).